Optimizing Fluid Resuscitation and Preventing Fluid Overload in Patients with Septic Shock - Ravi, Chandni; Johnson, Daniel W. (Seminars in Respiratory and Critical Care Medicine, 2021)
Intravenous fluid administration remains an important component in the care of patients with septic shock. A common error in the treatment of septic shock is the use of excessive fluid in an effort to overcome both hypovolemia and vasoplegia. While fluids are necessary to help correct the intravascular depletion, vasopressors should be concomitantly administered to address vasoplegia. Excessive fluid administration is associated with worse outcomes in septic shock, so great care should be taken when deciding how much fluid to give these vulnerable patients. Simple or strict “recipes” which mandate an exact amount of fluid to administer, even when weight based, are not associated with better outcomes and therefore should be avoided. Determining the correct amount of fluid requires the clinician to repeatedly assess and consider multiple variables, including the fluid deficit, organ dysfunction, tolerance of additional fluid, and overall trajectory of the shock state. Dynamic indices, often involving the interaction between the cardiovascular and respiratory systems, appear to be superior to traditional static indices such as central venous pressure for assessing fluid responsiveness. Point-of-care ultrasound offers the bedside clinician a multitude of applications which are useful in determining fluid administration in septic shock. In summary, prevention of fluid overload in septic shock patients is extremely important, and requires the careful attention of the entire critical care team.
Keywords: septic shock; fluid resuscitation; fluid overload; point-of-care ultrasound; sepsis guidelines